Thiazole-carboxamide derivatives as potent antioxidant agents with drug-like properties: In vitro, molecular docking, and DFT studies - Mohammed Hawash; Dina Ghannam; Leen Dawoud; Mais Dawoud; Ahmed Eid; Lara Alhajj; Mohammed T. Qaoud (PLoS ONE, 2025)
The search for novel therapeutic agents with potent antioxidant and antidiabetic properties remains a critical area of research in medicinal chemistry. Oxidative stress, caused by an imbalance between free radicals and the body’s antioxidant defenses, is implicated in numerous diseases, including diabetes, cancer, and neurodegenerative disorders. The in vitro evaluation of the antioxidant activity and α-amylase inhibitory potential was conducted on a series of thiazole-carboxamide derivatives, among this series, the strongest antioxidant activity against the DPPH free radical was exhibited by LMH6, with an IC₅₀ value of 0.185 µM, followed by LMH7 with an IC₅₀ value of 0.221 µM. Notably, the positive control Trolox exhibited a comparatively higher IC₅₀ value of 3.10 µM, underscoring the exceptional antioxidant potential of the synthesized compounds. Upon evaluating the inhibitory potency of the LMH series against the α-amylase enzyme, as a measure of their potential antidiabetic activity, the compounds generally exhibited modest to weak activity. In this case, their inhibition profiles were notably less potent compared to the respective positive control (acarbose). Subsequently, molecular docking studies were conducted to explore potential mechanisms that may underlie the observed antioxidant and antidiabetic activities. While these in silico analyses suggest possible interactions, particularly with the Keap1 protein, they serve as complementary hypotheses rather than direct validation of the in vitro findings. Docking scores, MM-GBSA binding energies, and association patterns were recorded and studied. Also, a DFT study was conducted to gain deeper insights into the free radical scavenging potential of the most potent antioxidant in the LMH series. The evaluated thiazole-carboxamide derivative demonstrated enhanced antioxidant potential by surpassing the reference compounds in terms of EHOMO-LUMO gap, electron affinity (EA), and ionization potential (IP). It was also evaluated the druggability of the tested compounds using Lipinski’s Rule of Five (LRO5). This analysis helps determine their drug-like properties based on established physicochemical criteria. The analysis confirmed that all the derivatives (LMH1–LMH9) met the LRO5 criteria, indicating their potential as orally active drug candidates. The ideal drug-likeness characteristics of these derivatives support the findings, highlighting the need for further preclinical and biological studies. These molecules could greatly facilitate future therapeutic research and approval due to their beneficial properties.